Factors Affecting the Growth of Dry Fish Industry in West Bengal : An Empirical Study - Giri, Arunangshu; Biswas, Debasish (Arthshastra Indian Journal of Economics & Research, 2018)
Dry fish industry is one of the most significant industries in rural India. India is exporting 200 tonnes of dry fish per year to various parts of the country as well as to Myanmar, Bangladesh, etc. Dry fish is not only consumed by humans, but it is also rampantly used in feeding poultry and broilers firms. This industry is not getting proper opportunity to sell its products not only in the Indian market, but also in the international market as the government has not focused on this market by providing financial and marketing support with licenses to this sector. Millions of poor fishermen who are engaged in the small scale dry fish industry are passing through a very tough situation for their livelihood. Unavailability of few species, absence of storage facilities, lack of rural road infrastructure, lack of facilities of preservation process, insect infestations, absence of product-standard testing facilities, etc. are the biggest issues for this sector. This study attempted to investigate multifarious factors which are affecting the growth of the dry fish industry in India. We also checked the relationship between the growth of the dry fish industry and the overall development of the rural community in India, particularly in West Bengal. The study confirmed the positive relationship between the growth of the dry fish industry and the overall development of the rural community. This study also suggested various recommendations to ensure the growth of the dry fish industry, which would also lead to the development of the rural community in India, particularly West Bengal.